2017
DOI: 10.5489/cuaj.4632
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of bleeding in children undergoing circumcision with ketorolac administration

Abstract: Introduction: Circumcision is the most common surgical procedure performed by pediatric urologists. Ketorolac has been shown to have an efficacy similar to morphine in multimodal analgesic regimens without the commonly associated adverse effects. Concerns with perioperative bleeding limit the use of ketorolac as an adjunct for pain control in surgical patients. As such, we sought to evaluate our institutional outcomes with respect to ketorolac and postoperative bleeding. Methods: We retrospectively reviewed al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…They further commented that there was also an increase in sanguineous oozing requiring evaluation by the surgeon. 8 As a pharmacological agent, ketorolac has a small volume of distribution, is metabolized via the kidney, and has an elimination halflife of about 5 h in pediatric patients. 9 Due to this pharmacokinetic profile, the effects of ketorolac should be insignificant by 24 h, as 94%-97% of the drug will have been eliminated after this period of time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They further commented that there was also an increase in sanguineous oozing requiring evaluation by the surgeon. 8 As a pharmacological agent, ketorolac has a small volume of distribution, is metabolized via the kidney, and has an elimination halflife of about 5 h in pediatric patients. 9 Due to this pharmacokinetic profile, the effects of ketorolac should be insignificant by 24 h, as 94%-97% of the drug will have been eliminated after this period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al reported an increased incidence of bleeding events requiring medical attention after circumcision in patients who received ketorolac 0.5 mg/kg. They further commented that there was also an increase in sanguineous oozing requiring evaluation by the surgeon 8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also the risk of bleeding, renal impairment and gastritis and peptic ulceration when administered over several days. Bleeding was not an issue after breast surgery [23] but after circumcision the ketorolac group had more bleeding [24]. Unlike ketorolac the selective cyclooxygenase 2 inhibitors are not associated with bleeding but have a higher rate of thrombotic events and should be avoided in patients at risk ly leads to a plasma concentration of about 2 mcg/ml [37].…”
Section: Intravenous Ketorolacmentioning
confidence: 99%